Patient-Centered Medical Home Knowledge and Attitudes of Residents and Faculty: Certification Is Just the First Step - El Rayess, Fadya (J Grad Med Educ, 2015)
BACKGROUND: The patient-centered medical home (PCMH) is an accepted framework for delivering high-quality primary care, prompting many residencies to transform their practices into PCMHs. Few studies have assessed the impact of these changes on residents' and faculty members' PCMH attitudes, knowledge, and skills. The family medicine program at Brown University achieved Level 3 PCMH accreditation in 2010, with training relying primarily on situated learning through immersion in PCMH practice, supplemented by didactics and a few focused clinical activities. OBJECTIVE: To assess PCMH knowledge and attitudes after Level 3 PCMH accreditation and to identify additional educational needs. METHODS: We used a qualitative approach, with semistructured, individual interviews with 12 of the program's 13 postgraduate year 3 residents and 17 of 19 core faculty. Questions assessed PCMH knowledge, attitudes, and preparedness for practicing, teaching, and leading within a PCMH. Interviews were analyzed using the immersion/crystallization method. RESULTS: Residents and faculty generally had positive attitudes toward PCMH. However, many expressed concerns that they lacked specific PCMH knowledge, and felt inadequately prepared to implement PCMH principles into their future practice or teaching. Some exceptions were faculty and resident leaders who were actively involved in the PCMH transformation. Barriers included lack of time and central roles in PCMH activities. CONCLUSIONS: Practicing in a certified PCMH training program, with passive PCMH roles and supplemental didactics, appears inadequate in preparing residents and faculty for practice or teaching in a PCMH. Purposeful curricular design and evaluation, with faculty development, may be needed to prepare the future leaders of primary care.